2013
DOI: 10.1016/j.jaci.2013.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of chronic rhinosinusitis: State of the field and directions forward

Abstract: The etiology of chronic rhinosinusitis (CRS) remains unclear. Study of the genetic susceptibility to CRS may be a valuable strategy to understand the pathogenesis of this burdensome disorder. The purpose of this review is to critically evaluate the current literature regarding the genetics of CRS in a comprehensive fashion. The most promising findings from candidate gene studies include the Cystic Fibrosis Transmembrane Conductance Regulator gene (CFTR), as well as genes involved in antigen presentation, innat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0
11

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 156 publications
(275 reference statements)
1
100
0
11
Order By: Relevance
“…Investigators have nevertheless suggested a number of candidate genes associated with CRS, which has led to some interesting observations with intriguing implications. Reviews of genetics of CRS [615][616][617] have been presented elsewhere and identified genes are presented as a tabulated list (Table VII- 10).…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have nevertheless suggested a number of candidate genes associated with CRS, which has led to some interesting observations with intriguing implications. Reviews of genetics of CRS [615][616][617] have been presented elsewhere and identified genes are presented as a tabulated list (Table VII- 10).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous genetic polymorphisms have been statistically associated to CRS, mainly on the cystic fibrosis transmembrane conductance regulator gene (CFTR), as well as genes involved in antigen presentation, innate and adaptive immune responses, tissue remodeling, and arachidonic acid metabolism [95,96]. More recently, the association between CRS and some of these genetic variants has been replicated [97], and new genetic variations associated with CRS have been reported, such as those on the cluster of differentiation 8a (CD8A) gene [98] and the bitter taste receptor genes [99,100].…”
Section: Genetic Markersmentioning
confidence: 99%
“…This view supports the hypothesis that a preliminary airway remodeling impedes an adequate inflammatory reaction. When considering the specific context of CRS, the most promising findings from candidate gene studies include the cystic fibrosis trans-membrane conductance regulator gene and the genes involved in tissue formation and maturation [10].…”
Section: Inflammation Induces Remodeling or Vice Versamentioning
confidence: 99%